PFASs–restriction proposal commentary on ECHA’s Annex XV restriction report, proposal for a restriction, March 2023 - Klaus-Michael Wollin; Monika Batke; Georg Damm; Alexius Freyberger; Ursula Gundert-Remy; Aswin Mangerich; Jan G. Hengstler; Falko Partosch; Thomas Schupp; Anna Sonnenburg; Heidi Foth (Archives of Toxicology, 2023)

Long-term simulation of lead concentrations in agricultural soils in relation to human adverse health effects - Thomas Schupp; Georg Damm; Heidi Foth; Alexius Freyberger; Thomas Gebel; Ursula Gundert-Remy; Jan G. Hengstler; Aswin Mangerich; Falko Partosch; Claudia Röhl; Klaus-Michael Wollin (Archives of Toxicology, 2020)
Lead (Pb) exposure of consumers and the environment has been reduced over the past decades. Despite all measures taken, immission of Pb onto agricultural soils still occurs, with fertilizer application, lead shot from hunting activities, and Pb from air deposition representing major sources. Little is known about the intermediate and long-term consequences of these emissions. To gain more insight, we established a mathematical model that considers input from fertilizer, ammunition, deposition from air, uptake of Pb by crops, and wash-out to simulate the resulting Pb concentrations in soil over extended periods. In a further step, human oral exposure by crop-based food was simulated and blood concentrations were derived to estimate the margin of exposure to Pb-induced toxic effects. Simulating current farming scenarios, a new equilibrium concentration of Pb in soil would be established after several centuries. Developmental neurotoxicity represents the most critical toxicological effect of Pb for humans. According to our model, a Pb concentration of ~ 5 mg/kg in agricultural soil leads to an intake of approximately 10 µg Pb per person per day by the consumption of agricultural products, the dose corresponding to the tolerable daily intake (TDI). Therefore, 5 mg Pb/kg represents a critical concentration in soil that should not be exceeded. Starting with a soil concentration of 0.1 mg/kg, the current control level for crop fields, our simulation predicts periods of ~ 50 and ~ 175 years for two Pb immission scenarios for mass of Pb per area and year [scenario 1: ~ 400 g Pb/(ha × a); scenario 2: ~ 175 g Pb/(ha × a)], until the critical concentration of ~ 5 mg/kg Pb in soil would be reached. The two scenarios, which differ in their Pb input via fertilizer, represent relatively high but not unrealistic Pb immissions. From these scenarios, we calculated that the annual deposition of Pb onto soil should remain below ~ 100 g/(ha × a) in order not to exceed the critical soil level of 5 mg/kg. We propose as efficient measures to reduce Pb input into agricultural soil to lower the Pb content of compost and to use alternatives to Pb ammunition for hunting.

Internal threshold of toxicological concern values: enabling route-to-route extrapolation - Falko Partosch; Hans Mielke; Ralf Stahlmann; Burkhard Kleuser; Susan Barlow; Ursula Gundert-Remy (Archives of Toxicology, 2015)

Functional UDP-glucuronyltransferase 2B15 polymorphism and bisphenol A concentrations in blood: results from physiologically based kinetic modelling - Falko Partosch; Hans Mielke; Ursula Gundert-Remy (Archives of Toxicology, 2013)